Migration, Dispersal, and Gene Flow of Harvested Aquatic Species in the Canadian Arctic - Tallman, Ross F. (2020)
Migration occurs when key aspects of the life cycle such as growth, reproduction, or maintenance cannot all be completed in one location. The Arctic habitats are variable and Arctic species are often migratory. The predictable nature of migrations in both space and time allow Arctic people to harvest fishes and marine mammals. We describe migratory/dispersal behavior in four types of taxa from the Canadian Arctic: anadromous and freshwater fishes, marine fishes, marine invertebrates, and marine mammals. Patterns of migration are remarkably different between these groups, in particular between distances migrated, seasonal timing of migrations, and the degree of reproductive isolation. Migratory anadromous and freshwater fishes become adapted to specific locations resulting in complex life histories and intra- and inter-population variation. Marine mammals not only migrate longer distances but also appear to have distinct demographic populations over large scales. Marine fishes tend to be panmictic, probably due to the absence of barriers that would restrict gene flow. Migratory patterns also reflect feeding or rearing areas and/or winter refugia. Migratory patterns of harvested aquatic organisms in the Canadian north are extremely variable and have shaped the north in terms of harvest, communities, and culture.